PSI Hypothesis (Global Journal of Medical Research, 2021)
Throughout history, human beings have experienced supernatural events that created new religions, mythologies, etc. to frighten people into forcing them to obey the authority. Due to the progress in science and technology, life style, and the way of scientific thinking, superstitions, and empty beliefs are not anymore means to convince people. Human beings are looking for more concrete manifestations to believe. The belief would be replaced by the scientific mind. Belief is a cover over the questions or suspicions in mind. The reality is to clear the mind by reasonable thinking and explain all the parapsychological events scientifically so that abstracting without any concrete base would not be accepted. Instead, scientific based mind will be the true evidence to think on the parapsychological events.
Keywords: belief; cognitive bias; magic; psi; extrasensory perception; poltergeist; psychokinesis